Measuring Air Carrier Passengers' Values of Time by Trip Component. Issue 1 (2016) - Landau, Steven; Gosling, Geoffrey D.; Small, Kenneth; Adler, Thomas
This paper investigates how the value of airline passenger time varies by trip component and how the calculation of value of time can be related to capital investments specific to each component. Travel time is often a significant consideration in benefit–cost analysis for airport projects. The empirical results reported in this paper are based on a stated preference survey and subsequent model estimation. The survey used two conjoint exercises—one related to airport ground access and in-airport time components and a second covering attributes related to the flight itinerary. It was found that values of time differ by trip segment and travelers' trip purpose.